ПУБЛІЧНО-УПРАВЛІНСЬКИЙ ІНСТРУМЕНТАРІЙ ВИКОРИСТАННЯ ШІ ОРГАНАМИ ДЕРЖАВНОЇ ВЛАДИ У СФЕРІ ОБОРОНИ - Олена ВОЛЬСЬКА (Herald of Khmelnytskyi National University. Economic sciences, 2026)
The article provides a theoretical rationale and systematization of public management tools for the application of artificial intelligence (AI) by state authorities in the defense sector. It is noted that the public management system must address contemporary challenges and employ modern approaches to ensuring the state's defense capability. One such measure is the use of artificial intelligence, which will enhance the nation's power on the international stage, ensure state sovereignty, and help strengthen national security. While AI technologies are already widely used in the defense sector, there is a growing need to establish a comprehensive public management framework. This will enable public authorities not only to integrate advanced Defense-tech solutions but also to guarantee their legal transparency, safety, ethics, and alignment with strategic defense goals. As a result of the study, the public management toolkit for AI implementation in defense is systematized, and its four main clusters are analyzed: regulatory and legal, institutional and organizational, information and analytical, and human resources and investment. It is proven that integrating artificial intelligence into the defense sector is a complex and multifaceted process requiring synergy among technological, legal, ethical, and social aspects, serving as a foundation for national security and the post-war recovery of Ukraine.